Preservice to in-service: impact of structured peer group supervision in the training of school psychology interns. Issue 1 (2nd January 2020) - Stone, Mary; O'Donnell, Patrick; Williams, Stacy
ABSTRACT: Evidence-based frameworks of peer supervision training are needed to enhance the preparation and practice of future school psychologists. This quasi-experimental pilot study found that school psychology interns provided with direct instruction in and opportunities to practice peer supervision ( n = 6) developed similar levels of competency in completing academic and behavioral case studies as their counterparts who were exclusively provided with hierarchical supervision during internship ( n = 8). Additionally, interns with preservice exposure to peer supervision demonstrated significantly higher levels of engagement in peer supervision as early career school psychologists. Implications of these findings for training are explored.